Hydrodynamic loads on a restrained ROV under waves and current. (15th August 2021) - Gabl, Roman; Davey, Thomas; Cao, Yu; Li, Qian; Li, Boyang; Walker, Kyle L.; Giorgio-Serchi, Francesco; Aracri, Simona; Kiprakis, Aristides; Stokes, Adam A.; Ingram, David M.
Abstract: Remotely Operated (underwater) Vehicles (ROV) have a wide range of maritime applications, including repair and maintenance. Quantifying hydrodynamic loads is important for the design and control of these ROVs. A novel approach with eight tethers was used to restrain a commercially available ROV, namely the BlueROV2 (Blue Robotics, Torrance, USA), in the mid depth of the FloWave wave and current test tank. This experimental set-up allowed the measurement of the forces under realistic flow around the ROV without introducing significant interference. The paper presents the analysis of the load cell data as forces and moments in relation to the observed motion and rotation of the ROV. In addition to active propelled cases, a variation of current speed (up to 1 m/s) coming out of the four directions as well as different regular waves were tested. Three different distances of a cylindrical obstacle provided a quantification of the effect of flow shadowing from a structure in front of the ROV. The results can also be used as a validation experiment to expand the application of ROVs and the influence of obstacles based on numerical simulations. Highlights: Hydrodynamic loads measured experimentally on remotely operated vehicles. Quantified shadowing effects of cylinder in front of ROV. Validation experiment to support station keeping algorithms under realistic conditions.